Power Line Carrier (PLC) sebagai Media Pendeteksi Phasa Pelanggan Tegangan Rendah - Anang Dasa Novfowan; Mochammad Mieftah; Wijaya Kusuma; Slamet Nurhadi (Politeknik Negeri Malang, 2023)
With so many distribution substations and the number of household customers, most of whom are single-phase low voltage customers, customer phase verification becomes very important in the load balancing proces. The customer phase detection system that has been studied previously, using radio frequency communication media over the air, is considered less valid if used in border areas between 2 (two) distribution substations. It is felt that the low voltage customer phase detection method will be more valid if it is carried out via Power Line Carrier (PLC) media, namely data communication via electrical lines. And this system consists of two devices, namely a transmitter (called the Master) which is installed on the LV Panel and a receiver (called the Slave) which is carried by the mobile to the detected phase point Short distance phase detection using Power Line Carrie from transmitter to receiver has a 100% success rate in one sub-panel with a transfer speed of 9600 baudrate, with an average detection time for short distances of 5 seconds. For long distance detection, sometimes the detection time is relatively long (± 120 seconds) or even failed, possibly due to the quality of the connection along the conductor being detected, thus causing noise in the network.